GLOBAL E-LEARNING AND EXPERIENTIAL OPPORTUNITIES FOR PROGRAMS AND STUDENTS: Received: 17th January 2023; Revised: 05th March 2023, 19th April 2023; Accepted: 24th April 2023 - Milligan, Meg; Paquette, Paige (PEOPLE: International Journal of Social Sciences, 2023)
Electronic learning (e-learning), pedagogy using online technology without physical proximity among the people involved, accelerated due to the recent pandemic and continues its metamorphosis in our endemic world. This new world creates new opportunities to apply e-learning in global contexts, by itself or blended with traditional methods as conditions warrant. Four iterations of a model are described and discussed in terms of adaptability, student satisfaction variables, development of intercultural competence, and global identity. The newest iteration combines previous iterations' e-learning and experiential learning opportunities with participants' occupational and program-specific experiences. The authors include testable outcomes and future possibilities.